Kinerja Tenaga Medis di Instansi Pelayanan Kesehatan: Pelayanan Prima, Kepuasan Kerja dan Motivasi - Pratama, Wahyu Ardy; Andriani, Dewi; Sumartik, Sumartik (Yayasan Pendidikan Riset dan Pengembangan Intelektual (YRPI), 2024)
Human Resources (HR) are the main asset in an organization, so human resources (HR) or also called actors (people) must be empowered in a balanced and humane manner. Health Service Agencies need human resources or medical personnel to achieve goals. Human resource management has several goals, one of which is organizational goals or company goals and also to achieve employees' personal goals.The purpose of this study was to determine the Effect of Excellent Service, Job Satisfaction and Motivation on the Performance of Medical personnel in Health Service Agencie.. The approach used in this study was quantitative by distributing questionnaires to 52 respondents who were taken using one of the non-probability sampling techniques used, namely the total sampling or saturated sampling. The data analysis technique used multiple linear regression of the IBM SPSS version 24 software program with results obtained that answer the hypothesis that there is a partial and simultaneously influence of excellent service, job satisfaction and motivation on performance.